Evaluating a MALTU Extension for UbiComp and IoT Systems - Feitosa, Carlos Eduardo Almeida; Monteiro, Ingrid Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
In the Ubiquitous Computing (UbiComp) and Internet of Things (IoT) paradigms, systems have certain specific quality-of-use characteristics that traditional Human-Computer Interaction (HCI) evaluation methods may not be able to address, such as context-awareness, invisibility, attentiveness, calmness, mobility and synchronicity, considering that most HCI assessments were generally created to evaluate desktop systems. MALTU model evaluates usability and user experience based on comments left by users on social systems (e.g. Amazom, Mercado Livre, Facebook forums). This work presents an extention in the model to adress these quality characteristics. Before proposing the extension, three evaluations were peformed with the original MALTU. Then, three evaluators performed two evaluations each on the same smart device: the first was the application of the extended MALTU, and the second was a heuristic evaluation using a specific set of heuristics for UbiComp systems. After that, a focus group was held in order to verify if the extended MALTU was capable of identifying typical problems of ubiquitous devices considering its quality characteristics. The results indicate that the extension was able to identify interaction problems in ubiquitous devices, mainly related to usability and user experience, even with difficulties in understanding the concepts of quality characteristics of ubiquitous and IoT systems.